PENGARUH KEPUASAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PENYADAP KARET DI PTPN VII UNIT USAHA WAY BERULU - Ya’qub Rakhazoni; Wuryaningsih Dwi Sayekti; Begem Viantimala (Lampung University, 2019)
The aims of this studyare to analyzejob satisfaction, working motivation, and performance of rubber tappers andthe influence of job satisfaction and working motivation on the performance of rubber tappers.The research location was chosen purposively in PT Perkebunan Nusantara VII Way Berulu, Kebagusan Village, Gedongtataan Sub-District, Pesawaran District. Respondents were all 80 rubber tappers of PT Perkebunan Nusantara VII Way Berulu. Data were analyzed descriptively and using multiple linear regression. The results showed that job satisfaction of rubber tappers of Afdelling I and II PTPerkebunan Nusantara VII Way Berulu was in category of most satisfied, working motivation was in a good category, and the performance met the expectation. Job satisfaction and working motivation influenced the performance of rubber tappers in PT Perkebunan Nusantara VII Way Berulu.Key words: job satisfaction, performance, working motivation